Bacteriological Profile and Antibiogram of Bacteria in Sputum Culture of Iraqi Patients: A retrospective study - Dawood, Haider Noori; Zwain, Luma Abdalhady; Alqaraghuli, Haider Abdulhameed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
Background: viruses are responsible for a large proportion of lower respiratory tract infections (LRTIs). Other causes of LRTIs are bacteria: Streptococcus pneumoniae, Haemophilus influenzae, Klebsiella pneumoniae, and Staphylococcus aureus being the most common. Sputum samples are commonly used in the microbiological laboratory for diagnosing lower respiratory infections. Objective: The aim of this study to evaluate the causative bacteria and antibiotics sensitivity in culture of sputum samples. Patients Methods: A retrospective study performed in the microbiology department of Al Immamin Al Kahdimin Medical laboratory in Baghdad. The results of sputum cultures collected from the files between 2016 and 2019. A total number of 131 included in the study of adults and both sexes. Organisms were identified and tested for the antibiotic susceptibility did for selected cases which ordered by the doctor needed. Results: The number of 131 were enrolled. The age of patients was between 17-85 years with mean age 46.69. The higher incidence of patients between ages 51-60 years (21.4 %). The female were 40.5%, the male 59.5%. 65 (49.62%) patients from the medical ward, 50 (38.17) from respiratory care unit (RCU). Acinetobacter spp was the most common bacteria isolated, in forty four (33.59%) cases, which was resistant to most antibiotics. followed by Streptococcus pneumonia (22.90%), Pseudomonas aeruginosa (16.03%),Escherichia coli in eleven (8.40) cases, with variable antibiotics sensitivity and resistance. Conclusion: sputum culture and sensitivity may help in identifying the organism and choosing the antibiotic, which may be resistant to many drugs as in Acinetobacter spp.